Evaluasi Layanan Referensi di Kantor Perpustakaan Arsip dan Dokumentasi Kabupaten Kerinci Provinsi Jambi - Fadjria, Annisa Nurul; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
In this paper discussed about evaluation of reference services in Archive Library Office and Documentation Kerinci District Jambi Province. Purpose of writing this paper is: (1) describe input management of reference services; (2) describe output management of reference services; (3) describe outcome management of reference. Type of research evaluation of reference services which is conducted in this paper with using the method descriptive qualitative that is data obtained from observasion and live interview with librarian and reference services user. Based on research concluded things as follow: first, input management of reference services consists of: (1) evaluation reference service not yet routine, so still there are deficiencies in service, like lack of evaluation againts performace librarian and reference collection not complete. (2) libararian in management of reference less understand the desire and less helpful the reader in information research. second, ouput management reference service seen from the role of the librarian has not clearly visible function as mentor in finding information as well give instructions between information in reference source. Third, outcome management reference service has not shown yet the impression of satisfaction, so the progress of increasing knowledge in the utilization of information and its impact on information upgrades does not exist.Keywords: evaluation, services and references.